God's omnipotence and human freedom - A. van de Beek (Acta Theologica)
It is an honour for me to write an article in this volume for Pieter Potgieter. In South Africa much attention is given to the political figures who led the nation out of the house of apartheid. We can, however, hardly overestimate the role of the church in this. That was true for the origins of apartheid, and is also true for its abolition. As moderator of the Dutch Reformed Church, Potgieter played a central role in this process. I have great esteem for his courage in turning the course of history that his forefathers set in motion. Every person who has the blood of an African, be they white or be they black, knows what a mental struggle this implies.